Evaluasi Penanganan Muatan Curah Cair Crude Palm Oil (Cpo) yang Efektif dan Efisien pada PT. Energi Unggul Persada di Mempawah - Rahmawati Rahmawati; Andreas Subangkit (Port Management and Maritime Administration Journal, 2025)
CPO is the raw result of the oil extraction process from palm oil fruit. This substance is a rusty red liquid which has varying consistency characteristics depending on the ambient temperature conditions. The problems faced in handling CPO liquid bulk cargo are based on several factors, namely limited infrastructure, weather, distance and how the government regulates the sustainability of this industry at PT. Energi Unggul Persada. The aim of this research is to find out how the CPO liquid bulk transportation procedures are carried out by PT. Energi Unggul Persada, the main challenges faced in handling CPO liquid bulk cargo, as well as how government regulations and policies influence CPO liquid bulk cargo handling procedures and their impact on industrial desires at PT. Energi Unggul Persada. This type of research is qualitative research with descriptive methods. This research was carried out at PT. Energi Unggul Persada from February 2022 to April 2022. The data collection techniques used were interviews, observation, documentation. Meanwhile, the informants used as research were the Shipping Section Operational Experts and Field Coordinators PT. Energi Unggul Persada in Mempawah. The data that has been collected is then carried out by data reduction, data presentation and verification. The results of this research are first, the procedures that have been established by the company, namely, before loading begins, the surveyor and lodging master prepare the required documents such as: shipping instructions, ship shore checklist, dry certificate, and the tools used include: flexible hose, crane, floating line, and pump. To ensure that the quality of CPO / cargo meets standards, then during the loading process, the loading master supervises and is responsible for the implementation and smoothness of the loading activity. Second, the main challenges faced in the process of handling CPO liquid bulk cargo include the limited number of pipes, weather conditions at the jetty, and quite long line distances. Third, by committing to supporting a sustainable palm oil industry, the government is adjusting export levies on CPO and its derivatives, which are then channeled back to focus on developing the people’s palm oil industry.